The Double Disappointment of Heberto Padilla in "La mala memoria" (Anclajes, 2023)
La mala memoria, the autobiography of Heberto Padilla published in 1989, has been studied to date as a source of information on the controversy known as “the Padilla case” of 1971. But the work can also be studied as a testimony of the experience of direct contact of Latin American writers with Soviet socialism. That experience is decisive in the concrete ideological evolution of the Cuban poet. From this perspective, the famous “Padilla case” could be analyzed from the Sovietization of the Cuban revolution, which Heberto Padilla discovered early, nine years before the controversy, and which he explains in detail in La mala memoria.
Keywords: Heberto Padilla; La mala memoria; Cuban Revolution; Cold War; autobiography